The role of medicinal animals and plants to strengthen immunity against viruses: a review - Mushtaque Kausar; Muhammad Kabir; Muhammad Shoaib Kiani; Usman Attiq; Arshad Mahmood Abbasi; Musheerul Hassan; Rainer W Bussmann; Muhammad Shoaib Amjad; Md Arshad Ali; Muhammad Altaf (PEACE International Publishers, 2025)
Plants and animals play a vital role in the day-to-day life by providing food, medicine, and many more. Many species are only used for particular purposes, growing in the wild and many are cultivated. To maintain the survival of mankind, the knowledge of medicine is always important, which is continuously evolving through different discoveries and inventions with the passage of time. However, it is very important to understand that the pathogens which are the potential sources of diseases are also evolving by developing resistance against the available drugs; in this regard all across the globe people associated with the knowledge are always in search of novel drugs both at traditional and modern levels to get against these pathogens. The literature review covered the electronic and printed articles published. We used a multi-query search strategy. The results were selected after several search passes by qualitative evaluation of the number of results obtained and their relevance. During the COVID-19 pandemic, researchers around the globe invested their resources and time to find a way to get against the COVID-19 dispersion. Different studies were followed to investigate plants and animal species for naturally existing antiviral molecules or compounds. Clinically available drugs like hydroxychloroquine and azithromycin were also analyzed. To reduce the impacts of the disease, a healthy diet that includes animal and plantderived supplements was recommended. Mankind is developing healthcare, but many pathogens have developed resistance and species have evolved, posing a potential threat to mankind. Folk knowledge is essential to investigate molecular compounds, and several globally threatened wildlife species have medicinal value against the COVID-19 pandemic.